Detection of quasi-periodic oscillation in the optical light curve of the blazar S5 0716+714 - Haiyan, Yang; Xiefei, Song; Xiaopan, Li; Na, Jiang; Haitao, Yang; Yuhui, Luo; Li, Zhou; Yan, Cai (Astrophysics and space science, 2023)
We report the detection of a quasi-periodic oscillation (QPO) in the optical R -band light curve of the blazar S5 0716+714 spanning approximately 32 years. Using both the Weighted Wavelet Z-transform and Lomb-Scargle Periodogram methods, we identified a prominent QPO of 1060 ± 50 days at a 5 σ confidence level against the red noise background. Our findings align well with previous studies. We introduce a supermassive binary black hole (SMBBH) model to account for the observed QPO and estimate the binary system’s Keplerian orbit to be 0.0053 parsec, indicating S5 0716+714 as a notable subject for upcoming nanohertz gravitational wave studies.